2015
DOI: 10.1159/000375169
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Home Mechanical Ventilation: Living Conditions and Health-Related Quality of Life

Abstract: Background: The number of patients with invasive home mechanical ventilation (HMV) following unsuccessful weaning is steadily increasing, but little is known about the living conditions and health-related quality of life (HRQL) in these patients. Objectives: To establish detailed information on living conditions and HRQL in patients with invasive HMV. Methods: The Severe Respiratory Insufficiency Questionnaire (SRI) was used to measure specific HRQL aspects in addition to patient interviews on individual livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
1
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 22 publications
9
67
1
21
Order By: Relevance
“…Validity and reliability in quality of life research has been discussed (Macduff, ; Moons et al., ). Good validity and international relevance of this study is provided by using the SRI questionnaire, that has shown very good psychometric qualities and has been professionally adapted and translated into several languages (Duiverman, Wempe, Bladder, Kerstjens, & Wijkstra, ; Ghosh, Rzehak, Elliott, & Windisch, ; Huttmann et al., , p. 280; López‐Campos et al., ; MacIntyre et al., ; Markussen et al., ; Oga et al., ; Ribeiro, Ferreira, Conde, Oliveira, & Windisch, ; Struik et al., ; Windisch, ; Windisch et al., ). Reliability and rigour are provided through high‐quality clinical data from the LTMV registry.…”
Section: The Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Validity and reliability in quality of life research has been discussed (Macduff, ; Moons et al., ). Good validity and international relevance of this study is provided by using the SRI questionnaire, that has shown very good psychometric qualities and has been professionally adapted and translated into several languages (Duiverman, Wempe, Bladder, Kerstjens, & Wijkstra, ; Ghosh, Rzehak, Elliott, & Windisch, ; Huttmann et al., , p. 280; López‐Campos et al., ; MacIntyre et al., ; Markussen et al., ; Oga et al., ; Ribeiro, Ferreira, Conde, Oliveira, & Windisch, ; Struik et al., ; Windisch, ; Windisch et al., ). Reliability and rigour are provided through high‐quality clinical data from the LTMV registry.…”
Section: The Studymentioning
confidence: 96%
“…The largest improvements were observed in NMD and OHS patients in the ‘attendant symptoms and sleep’ domain (Windisch, ). Co‐morbidity was more prevalent in older patients with COPD, reducing their SRI score compared with younger patients with NMD (Huttmann, Windisch, & Storre, ). The physiological efficacy of the LTMV treatment is to decrease the work of breathing and support gas exchange (Georgopoulo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wenn außerklinische Versorgung bildet die Grundlage für eine adäquate medizinische Versorgung, sorgt aber auch für eine erhöhte Lebensqualität und Autonomie der Patienten [8,22,55]. Bei der invasiven Beatmung stehen neben der fachpflegerischen 1:1-Versorgung in dem gewohnten häuslichen Umfeld weitere Versorgungsformen wie Beatmungsheime oder auch Wohngemeinschaften zur Verfügung [21].…”
Section: Außerklinische Beatmungunclassified
“…RCT, multizentrisch RCT, "crossover" ACV "assisted volume ventilation", AHI Apnoe-Hypopnoe-Index, AI Arousal-Index, ALS amyotrophe Lateralsklerose, APCV "assisted pressure-controlled ventilation", AVAPS "average volume-assured pressure support", BiPAP "bilevel positive airway pressure", CCHS kongenitales zentrales Hypoventilationssyndrom, COPD "chronic obstructive lung disease", chronisch obstruktive Lungenerkrankung, CPAP "continuous positive airway pressure", FSHD fazioskapulohumerale Muskeldystrophie, HI-NPPV "high intensity non-invasive positive pressure ventilation", iVAPS "intelligent volume-assured pressure support", LI-NPPV "low intensity non-invasive positive pressure", LTOT "long-term oxygen therapy", Sauerstoff-Langzeittherapie, MG Myasthenia gravis, MM mitochondriale Myopathie, NIV "noninvasive ventilation", NMD "neuromuscular disease", OHS "obesity hypoventilation syndrome", PCV "pressure-controlled ventilation", pl-NPPV "pressure-limited non-invasive positive pressure ventilation", PNRS "prospective non-randomized controlled study", PS "pressure support", PSG Polysomnographie, PSV-VG "volume-guaranteed pressure support ventilation", RCT "randomized controlled trial", randomisierte kontrollierte Studie, REM "rapid eye movement", SMA spinale Muskelatrophie, SV "spontaneous ventilation", Spontanatmung, TBC Tuberkulose, TST "total sleep time", VPAP "variable positive airway pressure", VCV "volume-controlled ventilation", vl-NPPV "volume-limited non-invasive positive pressure ventilation" a Schlafqualität als primärer Endpunkt b Keine weiteren Informationen Patienten, die in Beatmungsheimen oder -wohngemeinschaften leben. Patienten mit neuromuskulären oder thorakalrestriktiven Erkrankungen scheinen dabei eine höhere gesundheitsbezogene Lebensqualität aufzuweisen als ältere multimorbide Patienten mit primär pulmonalen Erkrankungen [22]. In der Zusammenschau der aktuellen Studienlage zeigt sich, dass Patienten mit NMD eine hohe Lebensqualität aufweisen können, unabhängig davon, ob die Patienten eine invasive oder nichtinvasive Beatmungsform erhalten [22,29,36].…”
Section: Symptome Der Respiratorischen Insuffizienzunclassified
See 1 more Smart Citation